Heterose e capacidade combinatória de genótipos da coleção nuclear de arroz da Embrapa - Ramos, Mariana Rodrigues Feitosa (2015)
The success of plant breeding programs depends on the choice of progenitors capable of producing progeny with desired characteristics, which are the raw material for the genetic selection. This study aimed to evaluate the combining ability of two groups of genitors, composed of 12 genotypes of rice, selected based on the high grain yield performance in each location (Goiania and Boa Vista), and their respective crosses, through complete diallel cross scheme without reciprocals, in two generations (F2 and F7). The experimental design was a randomized blocks, and it were evaluated the traits grain yield (PG) and days to flowering (DF), and estimated the varietal effect ( ̂), the average heterosis, varietal heterosis ( ̂ ) and specific heterosis ( ̂ in every generation, and for each group, the general combining ability ( ̂ ) of the parents. Significant differences were detected among the parents of both groups, for both traits, and were considered the most promising for the selection of new inbred lines, the combinations involving genitors with the highest values and positive effects of ̂ For PG trait in Goiânia, it were identified Canela Curta, Maninjau, Epagri 108 and Diamante, and in Boa Vista, the best genotypes were BRS Jaburu, BG90-2, Mearim, BRS Biguá and Chililica. For the DF trait in Goiânia, the genitors showing a decrease in the number of days to flowering and increased ̂ were Araguaia, CT11632, IRAT 122, Pratinha Branco and TOx 503, while for Boa Vista it were TOx 514, BRS Jaburu, Itaqui , BG90-2, BRS Biguá and IR54R. The use of SSR markers to infer the potential success of a certain hybrid combination, both in F2 and F7 generation, has not been indicated for the group of genitors evaluated.